Keep it in the family - Marrs, John (Freelance journalist) (Thomas & Mercer, 2022)
"In this chilling novel from bestselling author John Marrs, a young couple's house hides terrible secrets - and not all of them are confined to the past. Mia and Finn are busy turning a derelict house into their dream home when Mia unexpectedly falls pregnant. But just when they think the house is ready, Mia discovers a chilling message scored into a skirting board: I WILL SAVE THEM FROM THE ATTIC. Following the clue up into the eaves, the couple make a gruesome discovery: their dream home was once a house of horrors. In the wake of their traumatic discovery, the baby arrives and Mia can't shake her fixation with the monstrous crimes that happened right above them. Haunted by the terrible things she saw and desperate to find answers, her obsession pulls her ever further from her husband. Secrecy shrouds the mystery of the attic, but when shards of a dark truth start to emerge, Mia realises the danger is terrifyingly present. She is prepared to do anything to protect her family - but is it already too late?"--